2022
DOI: 10.1167/iovs.63.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelium–Derived Netrin-1 Alleviates Dry Eye Disease via Regulating Dendritic Cell Activation

Abstract: Purpose To investigate the expression of corneal epithelium–derived netrin-1 (NTN-1) and its immunoregulatory function in dry eye disease (DED) using a DED mouse model. Methods We generated DED mouse models with desiccating stress under scopolamine treatment. RNA sequencing was performed to identify differentially expressed genes (DEGs) in the corneal epithelium of DED mice. NTN-1 expression was analyzed via real-time PCR, immunofluorescence staining, and immunoblotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Notably, the drug was mainly distributed in the epithelium of the cornea, which may benefit DED therapy as the DED was characterized by the abnormal corneal epithelium. 50
Figure 5 The effects of TAT modification on the retention of drugs in the cornea. ( a ) The changes of MT contents in the cornea, and ( b ) the calculated area under the curve (AUCs).
…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the drug was mainly distributed in the epithelium of the cornea, which may benefit DED therapy as the DED was characterized by the abnormal corneal epithelium. 50
Figure 5 The effects of TAT modification on the retention of drugs in the cornea. ( a ) The changes of MT contents in the cornea, and ( b ) the calculated area under the curve (AUCs).
…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 , 43 - 53 ] Numerous in vivo studies have confirmed similar altered status of DCs in cornea, conjunctiva and lacrimal gland, and its plausible contribution or mechanism to disease pathogenesis in DED. [ 54 - 60 ] The clinical relevance of DCs can be appreciated with its strong association with DED clinical parameters in patients and the mechanistic studies in the animal models of DED. As illustrated in Fig.…”
Section: Ocular Surface Immune Cell Profile In Dedmentioning
confidence: 99%
“…T cell subsets that were investigated in animal models of DED include CD4+ T cells,[ 70 , 76 , 82 - 84 ] CD8+ T cells,[ 76 ] central memory T cells,[ 85 ] effector memory T cells,[ 85 ] Th1 cells,[ 38 , 86 - 88 ] Th2 cells,[ 89 ] Th17 cells,[ 38 , 60 , 88 , 90 - 92 ] and T regulatory cells – Tregs. [ 38 , 39 , 86 , 90 , 91 ] Increase in ocular surface CD4+ T cells,[ 70 , 76 , 82 - 84 ] CD8+ T cells,[ 76 ] Th1 cells,[ 86 , 87 ] and Th17 cells,[ 60 , 88 , 90 - 92 ] and a decrease in the ocular surface Tregs,[ 86 , 90 ] have been observed in various DED animal models. Contrary to the observations made in a human study,[ 81 ] a decrease in naïve T cells and central memory, along with an increase in effector memory T cells in the eye tissues of DED animals.…”
Section: Ocular Surface Immune Cell Profile In Dedmentioning
confidence: 99%
See 2 more Smart Citations